Engels @ 200 Reading Friedrich Engels in the 21st Century - Jacob, Frank (Büchner-Verlag, 2020)
Friedrich Engels was one of the most important German thinkers of the 19th century and his writings are still important today. Addressing the pressing issues of his time, the broadly interested scholar Engels would write about many different topics, and thereby not only pave the way for a science-based socialism, but also for further studies in sociology, history, and philosophy. To highlight the value and impact of Engels' work as well as emphasize its relevance for major issues that will determine the 21st century, the present anthology assembles scholars from different countries and research fields to discuss how to read and gain insights from reading his works in our time. It also attempts to stimulate further research about Engels, who 200 years after his birth deserves to be fully brought out of the shadow of his friend and colleague Karl Marx.